2017
DOI: 10.11621/pir.2017.0302
|View full text |Cite
|
Sign up to set email alerts
|

On the challenge of polysemy in contemporary cognitive research: What is conscious and what is unconscious

Abstract: Background. The problem of polysemy has attracted scholars' attention since antiquity and interest in the phenomenon never lessens. A substantial number of works have been published on the cognitive nature of meaning ambiguity. Despite a new emphasis on the cognitive aspects of polysemy, little has been done towards an integrated approach to the study of this linguistic phenomenon. objective and method. This work's objective was to contribute to an integrated interdisciplinary theory of polysemy. To this end, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…The research revealed that polysemy among idiomatic expressions was not as regular or productive as synonymy (59%). This finding is in accordance with the data obtained by Boyarskaya and Zabotkina (2017), Dobrovol'skij and Piirainen (2018), and Ivanova (2017). The authors indicated that idioms' inherently evaluative and expressive nature, as well their extended lexical make-up prevented them from developing a ramified network of paradigmatic relations.…”
Section: Research Question 3 How Well Are Russian Learners Aware Of supporting
confidence: 93%
See 1 more Smart Citation
“…The research revealed that polysemy among idiomatic expressions was not as regular or productive as synonymy (59%). This finding is in accordance with the data obtained by Boyarskaya and Zabotkina (2017), Dobrovol'skij and Piirainen (2018), and Ivanova (2017). The authors indicated that idioms' inherently evaluative and expressive nature, as well their extended lexical make-up prevented them from developing a ramified network of paradigmatic relations.…”
Section: Research Question 3 How Well Are Russian Learners Aware Of supporting
confidence: 93%
“…That said, the posthoc interviews with the participants revealed that they guessed rather than knew the second meaning of a polysemous idiom. While guessing is a useful strategy for figuring out polysemous words' and expressions' meanings (Boyarskaya & Zabotkina, 2017), this may still result in a significant margin of error and may lead to appreciable communicative mistakes, which is inadmissible if much is at stake, not least the interpreter's reputation and/or integrity. Given this, we believe that a more rigorous methodical tool for singling out idioms' meanings should be proposed, such as the 'cognitive trace' criterion, discussed in Glucksberg (2001), or the context of usage, which may be definitive in teasing idiomatic meanings apart (Naciscione, 2010).…”
Section: Research Question 3 How Well Are Russian Learners Aware Of mentioning
confidence: 99%
“…Обзор научной литературы проведен на основе анализа работ по следующим проблемам: язык и культура как объект изучения в междисциплинарных областях -когнитивной лингвистике, психологии, биологии, педагогике [Беляев, 2016; Платон, 1990-1994]; (Hassan, 2014, Imai, Kanero, Masuda, 2016, Nakahashi, 2019), идиоматика языковой системы и сравнительносопоставительный анализ единиц разных уровней [Аксенова, 2017;Савицкий, 2006;Хонькина, 2010;Zabotkina, Boyarskaya, 2017]; кросс-культурная коммуникация, основанная на фоновых знаниях и культурных реалиях DOI: https://doi.org/10.25146/1995-0861-2020-52-2-215 УДК 37.011. 33 МЕЖЪЯЗЫКОВАЯ ИДИОМАТИЧНОСТЬ В ОНОМАСИОЛОГИЧЕСКОМ АСПЕКТЕ Л.Р.…”
unclassified